How can magnetoencephalography and magnetic resonance imaging improve our understanding of genetic susceptibility to Alzheimer's disease? - Heise, V (2013)
The Apolipoprotein E (APOE) ε4 allele is the best-established genetic risk factor for sporadic Alzheimer’s disease (AD) while the ε2 allele confers a reduced risk compared with the most common ε3 allele. Neuroimaging studies using magnetic resonance imaging (MRI) have shown that APOE genotype affects brain structure and function. The aims of the research presented in this DPhil thesis were twofold: 1) to investigate the effect of APOE genotype on brain function in healthy adults using magnetoencephalography (MEG), which is a direct measure of neuronal activity and 2) to explore interactions between the AD risk factors APOE ε4 allele, age and female gender and their effects on brain structure and function using resting-state functional MRI and diffusion tensor imaging. MEG revealed similar neuronal activity at rest for APOE ε2 and ε4 carriers, i.e. those with opposite AD risk, indicating a more general effect on the functional architecture of the brain that is not directly linked to AD risk. However, differences between APOE ε2 and ε4 carriers became apparent when reactivity to stimuli was explored using the excellent temporal resolution of MEG. APOE ε4 carriers showed faster sensory pro- cessing and APOE genotype effects were found for functional networks associated with attention. In the second part of this project, female APOE ε4 carriers showed overall significantly reduced functional connectivity between the hippocampus and precuneus and a significant age-related decrease in connectivity of these regions. Increased vulnerability of this connection might be one reason for increased AD risk and interventions targeting hippocampal connectivity might be especially effective in at-risk populations. The research presented in this DPhil thesis showed a complex pattern of APOE genotype effects on brain structure and function. While global APOE genotype effects on functional and structural connectivity do not follow patterns of AD risk, more specific measures of connectivity and task-related brain function could be of use in the development of preclinical markers for AD development.